Links between the Eurozone stock markets: A new perspective, considering the capitalization level - Vítor Gabriel; Helena Saraiva (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
Recent legalizations of cannabis at the state level in the United States have given rise to renewed interest in the price elasticity of demand for cannabis and implications for likely state excise and sales tax revenues. We use crowdsourced data on prices, qualities, and consumption of cannabis across regional markets in the United States to estimate the price elasticity of demand for cannabis. We use distances from growing areas to the major markets as a proxy for cost variations. We obtain an estimate of the price elasticity of demand for cannabis of -0.418, which suggests that legalizing and taxing recreational cannabis use would be lucrative for government treasuries.
Keywords: G11; G15; 330; european stock markets; cap segments; vector autoregressive; cointegration